ANALISIS KINERJA KEUANGANDILIHAT DARI CURRENT RATIO, DEBT TO EQUITY RATIO, DAN RETURN ON ASSETS PADA KOPERASI WANITA “SALIMA” KECAMATAN TUGUMULYOKABUPATEN MUSI RAWAS - Surajiyo Surajiyo (LPPM UNIVERSITAS BINA INSAN, 2018)
This study aims to determine financial performance. Based on the Regulation of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 20 / Per / M.KUKM / XI / 2008. The type of research conducted by descriptive quantitative. The data sources used are secondary data derived from financial statements in the form of balance sheets and profit and loss between 2012-2016. The data analysis technique in this study uses quantitative analysis, namely analyzing financial statements with a ratio approach, namely the current ratio, debt to equity ratio, and return on assets, then adjusted to the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 20 / Per / M .KUKM / XI / 2008. The results showed that based on the Regulation of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 20 / Per / M.KUKM / XI / 2008